1992
DOI: 10.2172/10106157
|View full text |Cite
|
Sign up to set email alerts
|

Fire tests to evaluate the potential fire threat and its effects on HEPA filter integrity in cell ventilation at the Oak Ridge National Laboratory, Building 7920

Abstract: Both the FRD and ORNL determined that the only way to obtain conclusive results and to accurately analyze the fire performance of the ventilation system, fire protection system, prefilters/HEPA filter array, FRP VOG duct, etc. was to design and conduct a full scale fire test series. In order to design and construct a representative test article, we had to gain an accurate and detailed understanding of the actual facility layout, fire protection systems, facility operating procedures, and ventilation system and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…An example of filter release studies is WHC (1996). Some filter tests with hydrocarbon fires have showed that the smoke cools before reaching the filters and particulate loading is not too severe (Hasegawa, 1992), but this result could be dependent on the amount of combustion mass.…”
Section: 2mentioning
confidence: 99%
“…An example of filter release studies is WHC (1996). Some filter tests with hydrocarbon fires have showed that the smoke cools before reaching the filters and particulate loading is not too severe (Hasegawa, 1992), but this result could be dependent on the amount of combustion mass.…”
Section: 2mentioning
confidence: 99%